CITRA KEMISKINAN DAN WATAK TOKOH DALAM CERITA PENDEK “ORANG KAMPUNG” KARYA JONI ARIADINATA TINJAUAN SOSIOLOGI SASTRA DAN RELEVANSINYA PADA PEMBELAJARAN BAHASA - Anis fitria; Moh. Ahsan Shohifur Rizal (Jurnal Tinta, 2021)
In the short story by Joni Ariadinata has an image of poverty and the character of the characters in it. In addition, the image of poverty and the character of the senidri figure has several types which will be discussed in this study. This study entitled "The image of poverty and the character of the character in the short story "orang kampung" by Joni Ariadinata, a review of the sociology of literature and its relevance to Indonesian language learning at the junior high and high school level" requires a problem formulation as well as the formulation of the problem, namely, 1. What is the image of poverty in the short story “The Villager by Joni Ariadinata? 2. What is the character of the character in the short story “The Villager by Joni Ariadinata? This type of research is a type of descriptive qualitative research. Qualitative research method is a research method based on postpositivism philosophy, this method is used to study natural objects. Where the researcher is the key instrument, the data collection technique is triangulated or combined, the data analysis is inductive/qualitative and the results of qualitative research emphasize meaning rather than generalization. Based on the data analysis carried out, it was concluded that the image of poverty and the character of the characters in the short story "The Villager by Joni Ariadinata has several types as listed above, and in a literary education there is a mutual need between a work and Indonesian, therefore literature and Language is a very important learning for the world of education.